GOTONG ROYONG CLEANS UP TOURIST AREA AT KERAKAT BEACH, EAST POHGADING VILLAGE - masbullah, masbullah (Universitas Darunnajah, Jakarta, Indonesia, 2023)
The beach is an interesting place as a place to do activities outside the home. The beauty of the beach must always be maintained so that comfort can still be obtained for everyone who visits it. The beach becomes a comfortable place if it is kept clean. East Pohgading Village is a place for tourism activities such as marine tourism, supporting facilities and white sandy beaches that are in great demand by tourists to visit. Public awareness, especially beach visitors at Kerakat Timur Pohgading Village, will maintain the cleanliness of the beach area and there is a need for public awareness in disposing of garbage in places that are not scattered around the beach. This community service activity aims to inspire visitors and traders on Kerakat beach to care about the environment. A well-maintained environment will be a good legacy for the next generation. Survey The results of the on-site research show that visitors understand waste and dispose of waste in its place.